William Flexion Exercise Education to Reduce Pain Levels Low back pain to Weavers at the Banjar Penulisan of Medahan, Gianyar - Ni Kadek Windi Wijayani; Safun Rahmanto (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
From the screening carried out at one of the weaving centers of Banjar, Tulis Medahan, it was found that 5 out of 6 weavers present had complaints of pain in their lower back, also known as low back pain. They don't know about low back pain yet. To add insight or knowledge from weavers, counseling is carried out about the meaning, causes, and factors that influence low back pain. Also given training on the benefits and forms of exercises that can be done independently at home, to reduce pain due to low back pain. Education for weavers about the William Flexion Exercise using leaflets as an outreach medium. Weavers are also given a pretest and posttest in the form of questions to measure the effectiveness of the counseling that has been given. The evaluation showed an increase in knowledge of weavers in counseling from 16% to 100% because counseling was easy to understand and went well.